Ископаемые жуки-щелкуны (Coleoptera, Elateridae) подсемейств Negastrinae и Cardiophorinae из верхней юры Каратау - Долин, В.Г. (Вестник зоологии, 1976)
Four new fossil genera with eight new fossil species of click beetles from Upper Jurassic of Central Asia (Karatau), belonging to recent Negastriinae and Cardiophorinae are described. It is shown that formation of the recent subfamilies of Elateridae began in Mesozoic. New fossil genus Pseudocardiophorites is very close to the recent Cardio-phorus Esch., but differs from it by a longer third segment of antenna only. The types and paratypes of the new species are in the collection of the Paleontological Institute of the Academy of Sciences of the USSR (Moscow).